Rwanda : Seventh Review Under the Policy Support Instrument, Request for a Three-Year Policy Support Instrument and Cancellation of Current Policy Support Instrument. (IMF Staff Country Reports; Country Report, 2013)
This paper discusses Rwanda's Seventh Review Under the Policy Support Instrument (PSI), Request for a Three-Year PSI and Cancellation of Current PSI. Progress under the PSI has continued to be satisfactory. Except for the ceiling on nonconcessional borrowing (NCB), all quantitative assessment criteria were met. All indicative targets and structural benchmarks were also met. The nonobservance of the NCB ceiling came about when the authorities allowed Rwandair to contract a new USD 50.7 million external loan in July. Presently, the IMF staff recommends a waiver on the basis of the authorities' commitment to prevent any reoccurrence.